2014
DOI: 10.1098/rstb.2013.0550
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of epiblast stem cells to Nodal and Activin signalling: a paradigm of early endoderm development in the embryo

Abstract: Mouse epiblast stem cells (EpiSCs) display temporal differences in the upregulation of Mixl1 expression during the initial steps of in vitro differentiation, which can be correlated with their propensity for endoderm differentiation. EpiSCs that upregulated Mixl1 rapidly during differentiation responded robustly to both Activin A and Nodal in generating foregut endoderm and precursors of pancreatic and hepatic tissues. By contrast, EpiSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 62 publications
4
9
0
Order By: Relevance
“…We further applied zip code mapping to identify the epiblast cells that are developmentally similar to the epiblast stem cells (EpiSCs). In agreement with our previous finding that EpiSCs are congruent with the anterior primitive streak cells of the midgastrulation embryo (Kaufman-Francis et al, 2014;Kojima et al, 2014a), cells of ten embryo-derived EpiSC lines and one ES cell-derived EpiSC line (ESD-EpiSC) (Zhang et al, 2010) were mapped to epiblast cell populations that encompassed those in the distal posterior domains (1P-4P) (Figures 7H, i-iii and 1F). Interestingly, EpiSCs with enhanced mesendoderm propensity displayed the transcriptome characteristics more of the posterior epiblast (the presumptive mesoderm and endoderm progenitors in the anterior primitive streak, Figure 7H iii; cf.…”
Section: Zip Code Mapping Of Single Cells and Embryo-derived Stem Cellssupporting
confidence: 91%
“…We further applied zip code mapping to identify the epiblast cells that are developmentally similar to the epiblast stem cells (EpiSCs). In agreement with our previous finding that EpiSCs are congruent with the anterior primitive streak cells of the midgastrulation embryo (Kaufman-Francis et al, 2014;Kojima et al, 2014a), cells of ten embryo-derived EpiSC lines and one ES cell-derived EpiSC line (ESD-EpiSC) (Zhang et al, 2010) were mapped to epiblast cell populations that encompassed those in the distal posterior domains (1P-4P) (Figures 7H, i-iii and 1F). Interestingly, EpiSCs with enhanced mesendoderm propensity displayed the transcriptome characteristics more of the posterior epiblast (the presumptive mesoderm and endoderm progenitors in the anterior primitive streak, Figure 7H iii; cf.…”
Section: Zip Code Mapping Of Single Cells and Embryo-derived Stem Cellssupporting
confidence: 91%
“…The six core mRNAs have, indeed, also previously been reported to be involved in diverse CSC-related properties, ranging from proliferation, migration and invasion, chemoresistance and tumorigenicity (see Table 4 for full references). Importantly, pluripotency-associated properties have also been demonstrated in other reports [69][70][71][72][73]. The six core mRNAs may further be implicated to be linked with four major signaling pathways that modulate numerous CSC-associated properties observed in the CRC spheroids ( Figure 6).…”
Section: Discussionsupporting
confidence: 71%
“…There have been reports of differing biological activity of Activin and Nodal. Chen et al found that the quality of endoderm induced by activin differed from that induced by NODAL, 76 and Tam and coworkers 77 showed that epiblast stem cells respond differently to activin compared to NODAL. As noted above, even in the presence of high doses of Activin or TGF‐β under defined conditions, hPSCs still display neural lineage priming across most of the population, suggesting that the suppression of neural specification mediated by Nodal signaling is incomplete under these conditions.…”
Section: Are Nodal and Activin Signaling Bioequivalentmentioning
confidence: 99%